2007
DOI: 10.1103/physrevlett.98.180403
|View full text |Cite
|
Sign up to set email alerts
|

Modified Coulomb Law in a Strongly Magnetized Vacuum

Abstract: We study electric potential of a charge placed in a strong magnetic field B ≫ B0 = 4.4 · 10 13 G, as modified by the vacuum polarization. In such field the electron Larmour radius is much less than its Compton length. At the Larmour distances a scaling law occurs, with the potential determined by a magnetic-field-independent function. The scaling regime implies short-range interaction, expressed by Yukawa law. The electromagnetic interaction regains its long-range character at distances larger than the Compton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 25 publications
7
46
2
Order By: Relevance
“…Up to this explicit novel dependence on θ , the potential V 2 (R, θ ) from (1.3) is comparable with the potential (1.1) from [3]. The consequences of the θ dependence will be also discussed in Section 4.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Up to this explicit novel dependence on θ , the potential V 2 (R, θ ) from (1.3) is comparable with the potential (1.1) from [3]. The consequences of the θ dependence will be also discussed in Section 4.…”
Section: Introductionmentioning
confidence: 60%
“…Recently, this potential is calculated in [3] and [1]. In [3], it is shown that the standard Coulomb law is modified by the vacuum polarization arising in the external magnetic field. This implies a short range character of interaction, expressed as Yukawa law…”
Section: Introductionmentioning
confidence: 99%
“…Using the ring improved effective potentials in the IR and the static limit, the gap equation, the dynamical mass and the critical temperature T c of QED in the LLL are determined. To have a first estimate on the efficiency of the improved IR limit in decreasing the critical temperature arising from one-loop effective potential in the ladder approximation, T (1) c , we will compare the ratio u ≡ T magnetic field is of order 10 13 − 10 15 Gauß (see [26] and the references therein). It is also relevant in the heavy ion experiments, where it is believed that the magnetic field in the center of gold-gold collision is eB ∼ 10 2 − 10 3 MeV 2 or B ∼ 10 16 − 10 17 Gauß [27].…”
Section: Introduction a Motivationmentioning
confidence: 99%
“…The role of screening of the Coulomb interaction in MF has a long story, see e.g. [8][9][10][11][12][13][14] for atomic systems.…”
Section: One-gluon Exchange In Mfmentioning
confidence: 99%
“…These topics are important in astrophysics of neutron stars [3][4][5][6], in cosmological theories [7], in atomic physics [8][9][10][11][12][13][14][15] in the physics of heavy ion collisions [16,17], and in the high-intensity lasers [18].…”
Section: Introductionmentioning
confidence: 99%